2022
DOI: 10.3390/jcs6030086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical and Wear Properties of Al 5059/B4C/Al2O3 Hybrid Metal Matrix Composites

Abstract: There is a developing interest in efficient materials in automobile and aerospace fields that involves the improvement of metal matrix composites (MMCs) with great properties which incorporate higher strength, hardness and stiffness, better wear and destructive resistance along with better thermal properties. This work deals with the evaluation of the mechanical and wear properties of the newly developed hybrid MMC of Al 5059/B4C/Al2O3 produced by stir casting method. The main aim of the work was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Smooth surfaces with a reduction in grain size were also achieved in specimens H6 , H8 and H9 owing to the proper selection of stirrer speed, melting temperature and reinforcement weight percentages. Similar results have been reported by various researchers (Murugan et al , 2017; Shuvho et al , 2020; Singh and Kaur, 2020; Anandaraj et al , 2021; Pranavi et al , 2022).…”
Section: Resultssupporting
confidence: 92%
“…Smooth surfaces with a reduction in grain size were also achieved in specimens H6 , H8 and H9 owing to the proper selection of stirrer speed, melting temperature and reinforcement weight percentages. Similar results have been reported by various researchers (Murugan et al , 2017; Shuvho et al , 2020; Singh and Kaur, 2020; Anandaraj et al , 2021; Pranavi et al , 2022).…”
Section: Resultssupporting
confidence: 92%
“…Metal matrix composites (MMCs) havebroad applications [1,2]. Aluminum is the preferred matrix material [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mechanical properties of Al2O3-based composites can be tailored by varying the content of other materials. For instance, evaluated the mechanical properties of metal matrix composites with different weight proportions of ceramic particles, including Al2O3, and found that the mechanical properties varied with the weight proportions of the ceramic particles [5]. This suggests that the mechanical properties of Al2O3based composites can be optimized by adjusting the composition of the composites.…”
Section: Introduction *mentioning
confidence: 99%